Proceedings of the Fourth International Conference on Learning Analytics and Knowledge 2014
DOI: 10.1145/2567574.2567589
|View full text |Cite
|
Sign up to set email alerts
|

Customized course advising

Abstract: Every college student registers for courses from a catalog of numerous offerings each term. Selecting the courses in which to enroll, and in what combinations, can dramatically impact each student's chances for academic success. Taking inspiration from the STEM Academy, we wanted to identify the characteristics of engineering students who graduate with 3.0 or above grade point average. The overall goal of the Customized Course Advising project is to determine the optimal term-by-term course selections for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Limited research does demonstrate that when students are taking a STEM course perceived to be difficult, enrollment in a second difficult course predicts a performance decrease in the first course, 64 and that engineering students' performance in precalculus may be weakened when concurrently taking a chemistry course versus taking another engineering course. 65 ■ RESEARCH QUESTIONS This study combined four major predictive factors that have been extensively studied independently within the literature for their roles in predicting undergraduate general chemistry success. These included prior course grades, mathematicsrelated factors, collaborative learning, and student demographics.…”
Section: ■ Review Of the Literaturementioning
confidence: 99%
“…Limited research does demonstrate that when students are taking a STEM course perceived to be difficult, enrollment in a second difficult course predicts a performance decrease in the first course, 64 and that engineering students' performance in precalculus may be weakened when concurrently taking a chemistry course versus taking another engineering course. 65 ■ RESEARCH QUESTIONS This study combined four major predictive factors that have been extensively studied independently within the literature for their roles in predicting undergraduate general chemistry success. These included prior course grades, mathematicsrelated factors, collaborative learning, and student demographics.…”
Section: ■ Review Of the Literaturementioning
confidence: 99%
“…As detailed by Lonn, McKay, & Teasley (2017), U-M had built a nascent learning analytics community with many research projects being launched to investigate a variety of questions related to student learning and academic success. For example, one project revealed that first-year engineering students who received a 4 on their Math AB Advanced Placement (AP) exam only received an A or B grade 50% of the time when enrolling in Calculus II their first term (Nam, Lonn, Brown, Davis, & Koch, 2014). A different project analyzed the impact of a general chemistry prerequisite on later student achievement and progression in subsequent chemistry courses (Shultz, Winschel, & Gottfried, 2015).…”
Section: Institutional Context and Rationalementioning
confidence: 99%
“…As for the supplementary sample, several interesting assistance works correspond to: a customized course advising to determine the optimal term‐by‐term course selections for students based on their incoming traits and previous course history and performance (Nam, Lonn, Brown, Cinda‐Sue, & Darryl, ), a design research process for a manipulative‐based fractions intervention program (Mendiburo, Sulcer, & Hasselbring, ), using learner promotions of content to identify quality content and implications for students and instructors (Gunnarsson & Alterman, ), time management (Ferguson & Clow, ; Jo, Kim, & Yoon, ; Kovanovic et al, ; Miyamoto et al, ; Tabuenca et al, ; You, ), and curriculum design (Dunbar, Dingel, & Prat‐Resina, ; Méndez, Ochoa, Chiluiza, & de Wever, ; Monroy, Snodgrass, & Whitaker, ).…”
Section: Applicationsmentioning
confidence: 99%